A Comparison of Second Order and Non-Second Order Limit Language Generated by Yusof-Goode Splicing System - Muhammad Azrin, Ahmad; Nor Haniza, Sarmin; Wan, Heng Fong; Yuhani, Yusof (Penerbit Universiti Teknologi Malaysia, 2015)
DNA splicing process is a study on the recombinant behavior of double-stranded DNA molecules with the existence of restriction enzyme and ligase. Head introduced the first mathematical model of splicing systems by using the relation of informational macromolecules and formal language theory. In addition, a few laboratory experiments have been conducted in order to verify certain types of splicing language called inert/adult, transient and limit language. Previously, researchers have focused on those types of splicing languages. Recently, an extension of limit languages namely second order limit language has been introduced. In this paper, the difference between second order limit languages and non-second order limit languages is depicted in some examples. Then, the formations of second order limit language in Yusof-Goode splicing system are investigated.